In vitro discovery of a human monoclonal antibody that neutralizes lethality of cobra snake venom. Issue 1 (31st December 2022) - Ledsgaard, Line; Laustsen, Andreas H.; Pus, Urska; Wade, Jack; Villar, Pedro; Boddum, Kim; Slavny, Peter; Masters, Edward W.; Arias, Ana S.; Oscoz, Saioa; Griffiths, Daniel T.; Luther, Alice M.; et al.
ABSTRACT: The monocled cobra ( Naja kaouthia ) is among the most feared snakes in Southeast Asia due to its toxicity, which is predominantly derived from long-chain α-neurotoxins. The only specific treatment for snakebite envenoming is antivenom based on animal-derived polyclonal antibodies. Despite the lifesaving importance of these medicines, major limitations in safety, supply consistency, and efficacy create a need for improved treatments. Here, we describe the discovery and subsequent optimization of a recombinant human monoclonal immunoglobulin G antibody against α-cobratoxin using phage display technology. Affinity maturation by light chain-shuffling resulted in a significant increase in in vitro neutralization potency and in vivo efficacy. The optimized antibody prevented lethality when incubated with N. kaouthia whole venom prior to intravenous injection. This study is the first to demonstrate neutralization of whole snake venom by a single recombinant monoclonal antibody, thus providing a tantalizing prospect of bringing recombinant antivenoms based on human monoclonal or oligoclonal antibodies to the clinic.